An effective combination catalyst of CeO2 and zeolite for the direct synthesis of diethyl carbonate from CO2 and ethanol with 2, 2-diethoxypropane as a dehydrating agent. Issue 21 (13th October 2020) - Chang, Tao; Tamura, Masazumi; Nakagawa, Yoshinao; Fukaya, Norihisa; Choi, Jun-Chul; Mishima, Takayoshi; Matsumoto, Seiji; Hamura, Satoshi; Tomishige, Keiichi
Abstract : The combination of CeO2 and H-FAU zeolite acted as an effective heterogeneous catalyst for the direct synthesis of diethyl carbonate from CO2 and ethanol with 2, 2-diethoxypropane as a dehydrating agent. Abstract : The combination catalyst of CeO2 and H-FAU zeolite was effective for the direct synthesis of diethyl carbonate from CO2 and ethanol with 2, 2-diethoxypropane as a dehydrating regent, where H-FAU catalyzed hydrolysis of 2, 2-diethoxypropane. The combination catalyst provided high activity and a high diethyl carbonate yield of 72% based on 2, 2-diethoxypropane at a low temperature of 393 K.